Osteoporosis in Adult Patients with Intellectual and Developmental Disabilities: Special Considerations for Diagnosis, Prevention, and Management. Issue 4 (April 2021) - Fritz, Rachel; Edwards, Linda; Jacob, Rafik
Abstract : Abstract: As medical care progresses, patients with intellectual and developmental disabilities are living longer and beginning to experience diseases that commonly afflict the aging population, such as osteoporosis. Osteoporosis and resultant fractures increase disability and threaten the independence of this vulnerable population. In addition, the diagnosis, prevention, and management of osteoporosis present unique challenges in these patients. Critical preventive targets include exercise modification, fall prevention, and monitoring for nutrient deficiencies. Commonly used in diagnosis and treatment monitoring, dual-energy x-ray absorptiometry (DXA) scan of the hip and spine may not be feasible, whereas peripheral DXA or computed tomography may be more accessible for patients with physical disabilities. Pharmacological treatment should be tailored to the individual patient, considering factors such as adherence and comorbidities. Finally, bone turnover markers are a noninvasive, cost-effective option for monitoring treatment response in patients who cannot undergo DXA. Abstract : The purpose of this literature review is to further explore osteoporosis (OP) in adults with intellectual and developmental disabilities (IDD). OP is a disease of particular importance because it may present earlier and with greater severity in patients with IDD. OP leads to skeletal fragility and an increased risk of fracture and is especially hazardous in patients with IDD because fractures increase morbidity and mortality and exacerbate existing disability. Clinical trials to determine safe and effective treatments for OP in this unique population are lacking, and there is a need for educational literature on this topic.